Absensi Perpustakaan Pengenalan Wajah Berbasis Open Computer Vision - Ikmal, Ikmal; Masnur, Masnur; Hamra, Hamra (Jurnal Sintaks Logika, 2025)
Conventional attendance methods have shortcomings, including manual student sign-ins, which are time-consuming and result in long queues at the library. The aim of this research is to develop a library attendance system that is fast and efficient. This study employs a qualitative approach through a literature review using the Python programming language and Visual Studio Code application. The web application development results in a library attendance system utilizing facial recognition technology, with features such as: login menu, attendance menu, student menu, and recognition menu. This attendance system speeds up and simplifies the service process for students in the library.